Das Phytoplankton . nach dem Material der Deutschen Tiefsee--Expedition 1898-1899. - Karsten, George, 1863-1937. ([Jena, G. Fischer, 1905)
Without general t.p. Issued in 3 parts, each with special t.p. Includes bibliographies. Das Phytoplankton des Antarktischen Meeres.--Das Phytoplankton des Atlantischen Oceans.--Das Indische Phytoplankton. Mode of access: Internet.